Utilization Of Soil Ameliorant To Control Emission In Oil Palm Plantation On Tropical Peat Soil - Thamrin; Hapsoh; Tandiono, Joko; Warningsih, Trisla (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
Development of oil palm plantation areas today is increasingly leading to marginal areas, particularly on peatlands. However, development of peatland as agricultural land or as oil palm plantation has the potential to cause peatland to change from a carbon sink into a source of carbon emission. This objective of this research to determine the effect of utilization soil ameliorant to oil palm yield production and in controlling carbon emission and its impact to soil peat chemical properties. The research was conducted in Rokan Hilir district, Riau. The study was carried out in a randomized block design with three replications and three levels of soil ameliorant. The results show that application of high rate soil ameliorant significantly increase FFB yield relatively from control plot. Based on observational data for two months after first application of boiler ash, the CO2 emission was tends to decrease in plot that get the application of soil ameliorant compared to the control plot. Application of 1.5 tonne/ha/yr of ameliorant give the lowest CO2 emission value. Improvement of soil peat chemical properties by application of boiler ash as soil ameliorant also observed in this study, where the high rate of soil ameliorant significantly improves soil pH and also tends to increase total Potassium and Cation Exchange Capacity (CEC).